1999
DOI: 10.1175/1520-0442(1999)012<2775:mttith>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Temperature Trends in the Himalaya and Its Vicinity: An Analysis Based on Temperature Records from Nepal for the Period 1971–94

Abstract: Analyses of maximum temperature data from 49 stations in Nepal for the period 1971-94 reveal warming trends after 1977 ranging from 0.06Њ to 0.12ЊC yr Ϫ1 in most of the Middle Mountain and Himalayan regions, while the Siwalik and Terai (southern plains) regions show warming trends less than 0.03ЊC yr Ϫ1. The subset of records (14 stations) extending back to the early 1960s suggests that the recent warming trends were preceded by similar widespread cooling trends. Distributions of seasonal and annual temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
457
2
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 726 publications
(518 citation statements)
references
References 30 publications
57
457
2
2
Order By: Relevance
“…0.19°C per decade in both the areas (p \ 0.05) between 1978 and 2009. This warming rate is slower than the average warming in Nepal (between 1971 and 1994) (Shrestha et al 1999) and in the Hindu Kush Himalayan region (between 1982 and 2006) (Shrestha et al 2012). …”
Section: Climatesupporting
confidence: 90%
“…0.19°C per decade in both the areas (p \ 0.05) between 1978 and 2009. This warming rate is slower than the average warming in Nepal (between 1971 and 1994) (Shrestha et al 1999) and in the Hindu Kush Himalayan region (between 1982 and 2006) (Shrestha et al 2012). …”
Section: Climatesupporting
confidence: 90%
“…Recent concerns about regional climate change have focused attention on the dependence of climate variables on elevation (Beniston and Rebetez 1996;Aizen et al 1997;Shrestha et al 1999;Liu and Chen 2000;Marchenko 1999;Giese and Moβig 2004;Bolch 2007). As far as the increasing rates of dependence of temperature on elevation is concerned, there are many contrasting results in the different mountainous regions.…”
Section: Discussionmentioning
confidence: 93%
“…As far as the increasing rates of dependence of temperature on elevation is concerned, there are many contrasting results in the different mountainous regions. In some mountainous regions, there is increased warming with increasing elevation (Beniston and Rebetez 1996;Aizen et al 1997;Shrestha et al 1999;Liu and Chen 2000). In contrast, some studies have shown that the rates of increase in temperature in the high elevation regions are lower than those in the low elevation regions (Marchenko 1999;Giese and Moβig 2004;Bolch 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These perceptions are supported by the historical records at Khudi station, which show that the minimum temperature increased 0.07 • C per year and the maximum temperature increased 0.02 • C per year from 1980 to 2012. Shrestha [46] reported a similar observation, that the mean annual temperature is estimated to increase by 0.06 • C annually and is projected to increase by another 1.2 • C by 2030, 1.7 • C by 2050 and 3.0 • C by 2100 in Nepal [47].…”
Section: Temperaturementioning
confidence: 99%